Association between fine particulate matter air pollution and acute aortic dissections: A time-series study in Shanghai, China. (March 2020) - Chen, Jinmiao; Lv, Minzhi; Yao, Wangchao; Chen, Renjie; Lai, Hao; Tong, Chaoyang; Fu, Weiguo; Zhang, Weijia; Wang, Chunsheng
Abstract: It remains unknown whether ambient air pollution could induce the onset of acute aortic dissection (AAD). This study aimed to investigate the potential association between fine particulate matter (PM2.5 ) and AAD onset. We collected new episodes of AAD between January 1, 2014 and December 31, 2018 from the emergency department of a major hospital in Shanghai, China. The overdispersed generalized additive model was used to estimate the association between PM2.5 and AAD emergency hospitalizations and was adjusted for time trends and weather conditions. During the study period, we identified a total of 1335 cases of AAD hospitalizations and recorded an average PM2.5 concentration of 45 ± 30 μg/m 3 . The association was statistically significant on the concurrent day of hospital admission, remained on the lag 1 day. For the average of the two lags, a 10 μg/m 3 increase of PM2.5 was associated with 3.38% (95% confidence interval: 1.02%, 5.79%) increase of AAD hospitalizations. The association between PM2.5 and AAD remained when adjusting for the concomitant exposures to coarse particulate matter, sulfur dioxide, nitrogen dioxide, carbon monoxide and ozone. The concentration-response curves increased apparently when daily PM2.5 concentration was beyond the China's National Ambient Air Quality Standard (35 μg/m 3 ). In stratified analyses, the significant association was only present among elders and males, and during cool season. This investigation demonstrated a significant and robust association between short-term PM2.5 exposure and increased AAD hospitalizations in Shanghai, China. Our findings have important implications for the prevention of AAD. Highlights: A significant association existed between PM2.5 exposure and increased AAD onset. The associations were stronger among elders and males and during the cool season. These findings had important implications for the prevention of AAD.